Analysis of Factors Inhibiting Students’ Problem-Solving Ability on Sequences and Series at SMA Negeri 2 Indramayu - Ihwan, Dinan Fadila; Ismunandar, Denni (Universitas Wiralodra, 2025)
This study is motivated by the persistently low level of students’ mathematical problem-solving ability in the topic of sequences and series, despite its importance in the senior high school mathematics curriculum. The purpose of this study is to identify and describe factors that inhibit students’ problem-solving ability in sequences and series at SMA Negeri 2 Indramayu from the perspectives of mathematics teachers. This research employed a descriptive qualitative approach involving several mathematics teachers at SMA Negeri 2 Indramayu. Data were collected through semi-structured interviews focusing on instructional methods, internal and external inhibiting factors, strategies implemented by teachers, and an overview of students’ problem-solving abilities. The findings indicate that teachers use a variety of instructional methods, including direct instruction, deep learning approaches, STAD-type cooperative learning, visual approaches, and GeoGebra; however, their implementation is constrained by time limitations and classroom conditions. Internal inhibiting factors include low learning motivation, students’ reluctance to engage, weak mastery of basic concepts, and difficulties in understanding word problems. External factors include limited learning facilities, less conducive classroom environments, and restricted instructional time. Teachers attempt to overcome these obstacles through interactive media, e-modules, educational games, personal approaches, scaffolding, and visualization, although these strategies have not yet been implemented optimally. These findings emphasize the need for more systematic, problem-solving-oriented lesson planning in teaching sequences and series.